Pengaruh Gaya Kepemimpinan Transformasional dan Ketersediaan Akses Digital Terhadap Kompetensi Digital Guru: Systematic Literature Review - Ridwan Abdullah; Nurhattati Nurhattati; Kamaludin Kamaludin (Journal on Education, 2025)
The issue of insufficient digital competence among teachers remains a problem in education today. The suboptimal implementation of transformational leadership and the lack of digital access have hindered the improvement of teachers' digital competencies. Transformational leadership and the availability of digital access are critical components influencing teachers' digital competence. The aim of this study is to examine the impact of transformational leadership style on teachers' digital competence, the impact of digital access availability on teachers' digital competence, and the combined effect of transformational leadership style and digital access availability on teachers' digital competence. This study uses the Systematic Literature Review (SLR) method to gather and review scientific literature on the influence of work-life balance and work-related stress on teachers' performance. The results indicate that transformational leadership style has a significant impact on teachers' digital competence, where school leaders who can optimize transformational leadership positively influence the improvement of teachers' digital competence. Additionally, the availability of digital access has a positive effect on teachers' digital competence. Transformational leadership style and digital access availability are interconnected in affecting teachers' performance. When both transformational leadership style and digital access availability are better optimized, teachers' digital competence will improve. These findings are crucial to understanding the influence of transformational leadership style and digital access availability on teachers' digital competence.